Organotypic Human Skin Cultures Incorporating Primary Melanocytes. Issue 9 (27th September 2022) - Roth‐Carter, Quinn R.; Koetsier, Jennifer L.; Broussard, Joshua A.; Green, Kathleen J.
Abstract: Three‐dimensional (3D) human organotypic skin cultures provide a physiologically relevant model that recapitulates in vivo skin features. Most commonly, organotypic skin cultures are created by seeding isolated epidermal keratinocytes onto a collagen/fibroblast plug and lifting to an air liquid interface. These conditions are sufficient to drive stratification and differentiation of the keratinocytes to form an epidermal‐like sheet with remarkable similarities to human epidermis. Coupled with genetic or pharmacological treatments, these cultures provide a powerful tool for elucidating keratinocyte biology. Recent focus has been placed on increasing the utility of organotypic skin cultures by incorporating other cell types that are present in the skin, such as melanocytes, immune cells, and other cells. Here we describe a step‐by‐step protocol for the isolation of neonatal human epidermal keratinocytes and melanocytes from foreskins, and the creation of organotypic skin cultures that include both cell types. We also describe methods that can be used to assess melanocyte behavior in these organotypic cultures, including methods for whole mount staining, measurement of melanocyte dendricity, staining for pigment, and 5‐bromo‐2′‐deoxyuridine (BrdU) labeling for identification of proliferating cells. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Isolation of primary cells Alternate Protocol : Isolation of primary cells using differential trypsinization Basic Protocol 2 : Organotypic culture protocol Support Protocol 1 : Culture and maintenance of NHEKs and melanocytes Support Protocol 2 : Lentiviral transduction of melanocytes Support Protocol 3 : Retroviral transduction of NHEKs Support Protocol 4 : Whole mount immunostaining protocol Support Protocol 5 : Measuring melanocyte dendricity Support Protocol 6 : Fontana‐Masson staining protocol Support Protocol 7 : BrdU labeling and staining